2010
DOI: 10.1177/1066480710372084
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Adaptation of the FACES IV Questionnaire: Psychometric Characteristics

Abstract: The aim of this study was to obtain a culturally adapted Spanish version of the American Family Adaptability and Cohesion Evaluation Scale (FACES IV). For this purpose, rigorous procedures were used in the retro-translation process and in the subsequent empirical study. The sampling consisted of 455 university students and a balanced scale of 13 items (α = .87) was obtained; a scale that can be used independently. Moreover, the study was rounded off with a 6-factor model that includes 2 central scales—cohesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
29

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 10 publications
6
49
1
29
Order By: Relevance
“…Previous reports on the internal consistency of the FACES enmeshment subscale are inconsistent. While some researchers have reported stronger internal consistencies than yielded in this study, ranging from .75 (Franklin et al 2001) to .77/.78 (Mirnics et al 2010;Olson 2011), to .89 J Child Fam Stud (Rivero et al 2010), other researchers have reported alpha coefficient estimates comparable to the one reported here, ranging from .65 (Marsac and Alderfer 2011) to .67 (Baiocco et al 2013).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Previous reports on the internal consistency of the FACES enmeshment subscale are inconsistent. While some researchers have reported stronger internal consistencies than yielded in this study, ranging from .75 (Franklin et al 2001) to .77/.78 (Mirnics et al 2010;Olson 2011), to .89 J Child Fam Stud (Rivero et al 2010), other researchers have reported alpha coefficient estimates comparable to the one reported here, ranging from .65 (Marsac and Alderfer 2011) to .67 (Baiocco et al 2013).…”
Section: Resultssupporting
confidence: 69%
“…In our study, only the enmeshed family functioning scale was analyzed, as per recommendations regarding how to use this tool in research settings, for which dimension scales are not appropriate (Olson 2010). The enmeshed subscale, which represents excessive bonding between family members, includes seven items (Olson 2011).…”
Section: Family Adaptability and Cohesion Evaluation Scale IV (Faces mentioning
confidence: 99%
“…In a previous study (Rivero, Martínez-Pampliega & Olson, 2010), the model of family functioning, with 4 items in each subscale was proved with good adjustment indexes χ 2 (237 N = 455) = 463.337, RMSEA = .046; CFI = .97; GFI = .92. Parallel to this, the model with one latent variable of family functioning was proved: χ 2 (244): 486,35, p < 0.001; GFI: .91, CFI:.…”
Section: Resultsmentioning
confidence: 98%
“…-FACES IV (Olson, Gorall y Tiesel, 2006): The Spanish version has 24 items divided in two balanced scales (cohesion and adaptability) and four unbalanced scales which measure the extremes of cohesion (enmeshed and disengaged) and of adaptability (chaos and rigidity), with 4 items each. The scales prove to be valid and have a suitable level of reliability (alpha: entre .77 y .50) (Rivero, Martínez-Pampliega & Olson, 2010). -Family Satisfaction Scale (Olson, Stewart y Wilson, 1990).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation